Hophornbeam copperleaf (Acalypha ostryifolia Riddell). (30th April 2020) - Sosnoskie, Lynn M.; Hayes, Robert M.; Steckel, Lawrence E.
Abstract : Hophornbeam copperleaf ( Acalypha ostryifolia Riddell) is an erect, herbaceous, dicot species in the Euphorbiaceae, or spurge, family that constitutes more than 200 genera and some 6, 000 species (Mayfield and Webster 2013). Although the euphorbs have a cosmopolitan distribution, none are found in the Arctic (Mabberley 1997). Members of the Euphorbiaceae may be trees, shrubs, herbs (occasionally aquatic), or vines; sometimes succulent and cactus-like; and often have glands on vegetative plant parts (Mabberley 1997; Zomlefer 1994). Genera in the spurge family include Croton, Euphorbia, Ricinus, and Acalypha. Acalypha consists of 450 species that are native to both the Eastern and Western hemispheres (Zomlefer 1994). Acalypha was the name used by Hippocrates because the leaves resemble those of nettles, whereas ostryifolia alludes to the resemblance of leaves to plants in the genus Ostrya (hophornbeam trees; Burrows and Tyrl 2013; Haddock 2014; Hilty 2018). As plants mature in the fall, the leaves can turn reddish-brown, which may indicate why "copperleaf" is included in the species' common name (Hilty 2018). Hophornbeam copperleaf is native to North America; it occurs in the United States ranging from Arizona east to Florida, north to Pennsylvania, and west to Nebraska (Anonymous 2019). It occurs in a variety of habitats including agronomic fields, cultivated areas, landscapes, roadsides, river and stream banks, thickets, pastures, and waste sites (Bryson and DeFelice 2010; Haddock 2014; Hilty 2018). This plant's other common names include copperleaf, pineland three-seed mercury, Virginia copperleaf, hornbeam mercury, hornbeam three-seed mercury, mercury, and rough-pod copperleaf (Bryson and DeFelice 2010; Haddock 2014; Hilty 2018; Steckel 2006).